2005
DOI: 10.1002/jmri.20389
|View full text |Cite
|
Sign up to set email alerts
|

Detection of acute renal ischemia in swine using blood oxygen level‐dependent magnetic resonance imaging

Abstract: Purpose:To determine the feasibility and sensitivity of blood oxygen level-dependent (BOLD) magnetic resonance imaging (MRI) to detect acute renal ischemia, using a swine model, and to present the causes of variability and assess techniques that minimize variability introduced during data analysis. Materials and Methods:BOLD MRI was performed in axial and coronal planes of the kidneys of five swine. Color R2* maps were calculated and mean R2* values and 95% confidence intervals (CIs) for the cortex and medulla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 20 publications
(17 reference statements)
1
25
0
1
Order By: Relevance
“…This is in line with other BOLD-MRI studies, showing little changes in cortical oxygenation in different situations 17,23 ; only extreme conditions, such as acute iatrogenic arterial obstruction in animal models, have been shown to significantly alter cortical R2*. 29 This is explained by the technical limitation of BOLD-MRI for renal cortex analyses. BOLD-MRI is less sensitive to changes in cortical PO 2 , because cortical blood PO 2 lies on the shoulder of the hemoglobin oxygenation curve, in contrast to medullary PO 2 , which lies on the linear part of the curve, and is more sensitive to small changes in oxygen tension.…”
Section: Pruijm Et Al Salt Intake and Renal Oxygenationsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with other BOLD-MRI studies, showing little changes in cortical oxygenation in different situations 17,23 ; only extreme conditions, such as acute iatrogenic arterial obstruction in animal models, have been shown to significantly alter cortical R2*. 29 This is explained by the technical limitation of BOLD-MRI for renal cortex analyses. BOLD-MRI is less sensitive to changes in cortical PO 2 , because cortical blood PO 2 lies on the shoulder of the hemoglobin oxygenation curve, in contrast to medullary PO 2 , which lies on the linear part of the curve, and is more sensitive to small changes in oxygen tension.…”
Section: Pruijm Et Al Salt Intake and Renal Oxygenationsupporting
confidence: 90%
“…Above a urinary sodium excretion of Ϸ300 mmol/d, medullary R2* appears to reach a plateau ( Figure 3A). In addition, at each level of sodium excretion, medullary R2* levels were lower in HT than NT individuals (mean: 29 Figure 3B). When analyzing blood pressure as a continuous variable rather than a dichotomous separator of groups, and independently of salt intake, an inverse correlation between the mean arterial blood pressure, as measured on the days of clearance and MR studies, and medullary R2* values was found (rϭϪ0.37; Pϭ0.026).…”
Section: Hypertensive Patientsmentioning
confidence: 92%
“…BOLD MRI has been used to investigate intra-renal oxygen bioavailability in the patients and experimental models of kidney diseases, such as water diuresis [5][6][7], diabetes [6], acute ischaemic renal dysfunction [8,9] and unilateral ureteral obstruction [10]. These studies provided evidence that BOLD MRI could effectively detect changes of intrarenal oxygen bioavailability in these diseases.…”
Section: Introductionmentioning
confidence: 91%
“…11,24,25 However, causation is more complex, since renal tissue hypoxia has been dissociated from hyperfiltration in experimental models of diabetes mellitus. 51 Experimental diabetes mellitus is also associated with mitochondrial dysfunction and reduced efficiency of oxygen utilization due to enhanced generation of reactive oxygen species, increased angiotensin II levels, and reduced nitric oxide availability.…”
Section: Neugarten and Golestanehmentioning
confidence: 99%